2019
DOI: 10.1016/j.ajo.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Topical 5-Fluorouracil and Interferon Alfa-2b as Primary Treatment Modalities for Ocular Surface Squamous Neoplasia

Abstract: Purpose: To compare the efficacy of topical 5-fluorouracil 1% (5FU) and interferon alfa-2b 1 MIU/mL (IFN) eye drops as primary treatment modalities for ocular surface squamous neoplasia (OSSN).Design: Retrospective, comparative, interventional case series.Methods: Fifty-four patients who received 5FU and 48 patients who received IFN as primary therapy for OSSN were included. Primary outcome measures were the frequency of clinical resolution and time to OSSN recurrence by treatment modality. Secondary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 55 publications
(64 reference statements)
0
75
0
2
Order By: Relevance
“…This study found that sub-clinical OSSN was detected by HR-OCT in 17% of patients whose tumors were noted to have resolved clinically. While the clinical implications of sub-clinical disease are unknown, OSSN recurrences are noted in 0-28% of eyes treated with 5-FU and in 4-20% of eyes treated with IFN [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It can be postulated that recurrences may be driving residual disease or sub-clinical disease, especially since most occurred within the first year after stopping treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that sub-clinical OSSN was detected by HR-OCT in 17% of patients whose tumors were noted to have resolved clinically. While the clinical implications of sub-clinical disease are unknown, OSSN recurrences are noted in 0-28% of eyes treated with 5-FU and in 4-20% of eyes treated with IFN [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It can be postulated that recurrences may be driving residual disease or sub-clinical disease, especially since most occurred within the first year after stopping treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Used in a recombinant form, administration of topical IFN alpha-2b (IFN α-2b) also leads to anti-proliferative and anti-angiogenic effects. IFN has successfully been administered for the treatment of other HPV-related diseases, such as genital papilloma, cervical intraepithelial neoplasia, and OSSN [86, 87]. Furthermore, it can be beneficial in highly vascularized carcinomas, although these mechanisms of action are not well understood [88].…”
Section: Main Textmentioning
confidence: 99%
“…Mitomycin C (MMC) is an alkylating agent derived from the actinobacterium Streptomyces caespitosus that exerts its anti-neoplastic effect by cross-linking DNA [104]. It has been used successfully in OSSN [86]. There is a paucity of data in its use for benign squamous papillomas.…”
Section: Main Textmentioning
confidence: 99%
“…intralesional versus topical interferon-a 2b , mitomycin C strength and regimen) that makes comparing these case series fraught with difficulty. Unsurprisingly, reported recurrence rates vary widely, from 0 to 56% with surgical excision alone [9][10][11][12][13], 0-28% with surgical excision followed by topical interferon-a 2b (IFNa 2b ) [12-20], 10-15% with surgical excision followed by topical 5-fluorouracil [16,21,22] and 0-30% with surgical excision followed by topical mitomycin C (MMC) [23][24][25][26][27][28]. From this potpourri of evidence, the clinician must formulate treatment strategies for a diverse patient population, often with many medical comorbidities.…”
Section: Introductionmentioning
confidence: 99%